The importance of the basic principles of rational emotive behavioural therapy in the educational process - Bozhok, Natalia (My University, 2014)
In the article the principles of rational emotive behavioural therapy are studied. This paper presents analysis of REBT in the educational process. The paper also outlines the peculiarities of ABC theory presented by REBT and shows its importance in developing students’ rational thinking and coping strategies with stresses and frustrations.
Keywords: rational thinking; ABC-аналіз; раціональне мислення; кафедра ділової іноземної мови та міжнародної комунікації